Seleucid-Parthian Adiabene in the Light of Ancient Geographical and Ethnographical Texts - Marciak, Michał (Anabasis. Studia Classica et Orientalia, 2011)
This paper surveys ancient texts in search of geographical and ethnographical information on Adiabene in the Seleucid and Parthian Periods. Adiabene originated as a relatively small province between the Lykos and Kapros rivers, perhaps including the Arrapachitis region. In the early Seleucid period, Adiabene was politically dependent on the mighty province of Babylonia. At some point in its Parthian history (between the mid–1 st century BCE and the mid–1 st century CE) Adiabene started to expand its territory northwest. From then on, it included Ashur and Nineveh, and extended along the eastern bank of the Tigris river to include Gordyene. Adiabene’s influence is also recorded on the western bank of the Tigris. In the first half of the 1 st century CE (incorporation between 37–40/41 CE) Nisibis belonged to Adiabene. Its influence on the western bank of the Tigris is also attested for the whole 2 nd century CE. As for Adiabene’s cultural profile, it featured a great deal of diversity, since it consisted of co-existing Iranian and Greek and Semitic elements.